The Relevance of Project-Based Lecture in Industrial Revolution 4.0 : Meta – Synthesis Study - Tristan Rokhmawan; Badriyah Wulandari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
The researchers conducted a meta-synthesis study of the concept of project-based lectures and the concepts of the development of the IR 4.0 era. The main goal of this study was to examine a rational relationship or relevance between the application of project-based lectures and the development of the educational paradigm in the Industiral Revolution (IR) 4.0 era. The result showed that the seventh project-based lecture features can realize the educational context in the IR 4.0 era. The result Meta-Synthesis in two concepts found seven relevances, namely: 1) Real study and essential supporting in freedom learning, broader learning context 2) Bureaucratic learning, relevant life to support freedom learning. 3) Learning inquiry based on investigative, complex to support students’ independence in learning. 4) Meaningful, social, and collaborative learning to support learning resources and good cooperation in learning. 5) Real-work learning and remember the process, supporting the contextuality and meaningful learning process. 6) Authentic learning and interdisciplinary, supporting the breadth and flexibility in developing knowledge accordance with the world developments. 7) Collaborative learning teachers, supporting of learning partnerships. Keywords: Project-Based Lectures, Industrial Revolution 4.0, Meta-Sythesis Study